Efficacy of Intralesional Vitamin D3 in the Treatment of Recalcitrant Common and Plantar Warts - حسن فوز; صهيوني ندى (Latakia University Journal -Medical Sciences Series, 2021)
Background: Recalcitrant warts represent a therapeutic challenge, with often disappointing response and high recurrence rates. Lately, treatment based on stimulating the cell-mediated immunity against HPV Virus has gained momentum. Vitamin D3 Receptors are found in keratinocytes and on immune system cells . Vitamin D3 has a role in Regulating epidermal cell proliferation, differentiation, and apoptosis. It also modulates the immune response by regulating cytokines, and Anti Microbial Peptides production. Patients and methods : forty patients with recalcitrant warts were included in the study. Vitamin D3 (1 mL, 300,000 IU/mL) was injected into the base of the warts after Lidocaine (0.5 mL, 20 mg/mL) injection. One wart, the greatest in diameter, was injected per session, in every clinically infected part . The sessions were at 2-week intervals until resolution of the injected wart or for a maximum of 4 treatments. Patients were followed up for 2 months after the last injection to evaluate complete Response. Results: 29 patients (72,5%) showed complete clearance of both injected and non-injected warts. 11 patients (27,5%) didn’t show complete clearance of those 2 patients showed partial response by clearance of only the injected warts, whereas 9 patients showed no response. Conclusion : Vitamin D3 is an effective, safe, and inexpensive method to treat recalcitrant common and palmoplantar warts.